1995
DOI: 10.1083/jcb.129.5.1329
|View full text |Cite
|
Sign up to set email alerts
|

The basal keratin network of stratified squamous epithelia: defining K15 function in the absence of K14.

Abstract: Abstract. Keratin 5 and keratin 14 have been touted as the hallmarks of the basal keratin networks of all stratified squamous epithelia. Absence of K14 gives rise to epidermolysis bullosa simplex, a human blistering skin disorder involving cytolysis in the basal layer of epidermis. To address the puzzling question of why this disease is primarily manifested in skin rather than other stratified squamous epithelia, we ablated the K14 gene in mice and examined various tissues expressing this gene. We show that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
256
3
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(280 citation statements)
references
References 47 publications
16
256
3
5
Order By: Relevance
“…On E18.5, the expression of K6 mRNA was weakly induced compared with wild-type mice, indicating that the induction of K6 mRNA was already initiated, possibly close to cytolyzing basal keratinocytes. Subsequent Western blotting demonstrated that the strong increase in K6 mRNA was also translated into the corresponding protein in neonatal mice, whereas we were unable to visualize K6 on E18.5 by this technique.The induction of K6 in K5 Ϫ/Ϫ mice seems to be in contrast to the K14 Ϫ/Ϫ mice (Lloyd et al, 1995). Whether this difference is due to the extent of tissue damage in both mice or whether there are other reasons remains to be clarified.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…On E18.5, the expression of K6 mRNA was weakly induced compared with wild-type mice, indicating that the induction of K6 mRNA was already initiated, possibly close to cytolyzing basal keratinocytes. Subsequent Western blotting demonstrated that the strong increase in K6 mRNA was also translated into the corresponding protein in neonatal mice, whereas we were unable to visualize K6 on E18.5 by this technique.The induction of K6 in K5 Ϫ/Ϫ mice seems to be in contrast to the K14 Ϫ/Ϫ mice (Lloyd et al, 1995). Whether this difference is due to the extent of tissue damage in both mice or whether there are other reasons remains to be clarified.…”
mentioning
confidence: 84%
“…Besides epidermis, we studied the keratin expression in tongue, esophagus, palate, fore stomach, foot, and tail (our unpublished results). In general, the intraepidermal cleft could be observed in every stratifying epithelium that we examined, emphasizing the extreme fragility of the basal cells as a consequence of the loss of K5.In contrast to K14 Ϫ/Ϫ and K6 Ϫ/Ϫ mice (Lloyd et al, 1995;Wong et al, 2000), the basal cells on the dorsal side of the tongue were largely unaffected ( Figure 5). Here, suprabasal expression of K6 was recently shown to be essential for the maintenance of epidermal integrity (Wong et al, 2000).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…EBS is characterized by cytoplasmic keratin aggregates, cytolysis of basal keratinocytes, and bullous lesions following mild trauma to the skin. Although it is recognized that the pathomechanisms contributing to EBS and additional keratinopathies are more complex than originally considered Roth et al 2012;Bohnekamp et al 2015;Hobbs et al 2016;Kumar et al 2016), it is evident that loss of an intact keratin cytoskeleton renders keratinocytes fragile on mild physical stress, shown by KRT5 and KRT14 KO mice (Lloyd et al 1995;Peters et al 2001). Of note, even mutations causing severe disease do not prevent formation of long keratin intermediate filaments (KIFs) in vitro (Herrmann et al 2002), suggesting that mutations and physical stress act at the level of keratin bundling, network organization, dynamics, or by affecting association with other proteins.…”
Section: Human Disease and Mouse Modelsmentioning
confidence: 99%